PEMANFAATAN MEDIA “WAYANG AKHLAK” SEBAGAI UPAYA MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN AKIDAH AKHLAK PADA PESERTA DIDIK KELAS VIII F MTs NEGERI 1 KEBUMEN TAHUN PELAJARAN 2018/2019 - Suyitman, M.Pd.I. (Madaris: Jurnal Guru Inovatif, 2021)
This study aims to describe the use of moral puppets in learning and to find out the increase in creativity and learning outcomes of moral character using moral puppet media. This research is a classroom action research with data collection instruments using observation and learning outcomes tests. Data analysis techniques using descriptive analysis and percentages. The application of moral puppets is not only as an introduction to the media to deliver material, but is also used from observation to communication. The forms of moral puppets can be made in various kinds such as cassava leaf puppets, grass puppet, straws puppet, picture puppets or other forms of puppets that can be made by students. Based on the results of the study, the use of moral puppets can increase student creativity. In Cycle I, the average creativity of students was only 65% and increased to 91% in Cycle II. Learning outcomes have increased. In Cycle 1, the average value of written test 1 was 79.00 and rose to 92.38 in Cycle II. Likewise for the written test score 2 and the performance which rose from 81.00 to 93.00 and 80.00 to 92.00. Thus, the use of moral puppets can increase the creativity and learning outcomes of students.